Wireless May Benefit Blockchain - Seungmo Kim; Junsung Choi (Applied Sciences)
Wireless technologies now take every part of one’s everyday life. As such, it will be no longer a surprise if a blockchain system is composed of wirelessly connected nodes. However, wireless communication is known for its inherent unreliability caused by noise, interference, limited bandwidth, etc. Motivated by this fundamental problem, this paper investigates the impact of wireless communications on the performance of three representative consensus mechanisms, viz., proof of work (PoW), proof of stake (PoS), and proof of coverage (PoC). It features a comprehensive analytical framework that mathematically derives metrics quantifying the scalability and the level of decentralization of the three consensus mechanisms, constituting a key contribution of this work. The paper then proceeds to present extensive simulation results as a means to confirm the underpinning theoretical findings. Overall, we emphasize that the framework’s holisticity will allow it to be applied to diverse consensus mechanisms.